2008
DOI: 10.1111/j.1532-5415.2007.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia, Diagnostic Disclosure, and Self‐Reported Health Status

Abstract: Further research is needed to elucidate the relationship between self-rated health and dementia specifically focusing on the potentially negative effects of diagnostic disclosure on self-rated health, further identification of factors that contribute to self-rated health in persons with dementia, and the prognostic value of self-rated health for persons with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Between one fifth and one third of people with dementia can recall their diagnostic label accurately (Pinner and Bouman, 2003;Elson, 2006;Campbell et al, 2008), although many more are able to recall some elements of the process of disclosure . Not surprisingly, recall of the diagnosis is associated with a higher Mini-mental State Examination (MMSE) score (Folstein et al, 1975), as well as younger age and higher levels of education; however, people with dementia who recalled their diagnosis were more likely to report poorer health status (Campbell et al, 2008).…”
Section: Factors Influencing Disclosure and Recall Of A Diagnosis Of mentioning
confidence: 99%
“…Between one fifth and one third of people with dementia can recall their diagnostic label accurately (Pinner and Bouman, 2003;Elson, 2006;Campbell et al, 2008), although many more are able to recall some elements of the process of disclosure . Not surprisingly, recall of the diagnosis is associated with a higher Mini-mental State Examination (MMSE) score (Folstein et al, 1975), as well as younger age and higher levels of education; however, people with dementia who recalled their diagnosis were more likely to report poorer health status (Campbell et al, 2008).…”
Section: Factors Influencing Disclosure and Recall Of A Diagnosis Of mentioning
confidence: 99%
“…We considered dementia to be present if the participant was taking a cholinesterase inhibitor or memantine. 23 We ascertained occurrence of pneumonia by self-report of hospitalization. A review of hospital records for a group of 94 participants showed excellent reliability for self-reported hospitalizations (κ=0.94).…”
Section: Methodsmentioning
confidence: 99%
“…In one study, patients with known dementia diagnoses were asked whether they have problems with memory and whether a physician had ever told them that they have a memory problem or dementia. Approximately 64% of participants reported memory problems, but only 26% reported having been previously told that they have memory problems or dementia by a physician 10 . There was also a sizeable discrepancy between patients and companions in their understanding of whether a dementia diagnosis had been given, with only 37% agreement between patient and companions.…”
Section: Introductionmentioning
confidence: 99%